ANALYSIS OF FATIGUE AMONG BAGGAGE HANDLERS USING THE FACIAL ACTION CODING SYSTEM (FACS) - Samuel Goesniady; Wilma Latuny (Universitas Trunojoyo Madura, 2023)
Baggage workers is a livelihood in the informal sector which is carried out by selling services to transport goods/materials from one place to another. The workload carried by the workers will determine how much income they receive in a day. For this reason, baggage workers tend to scramble to transport goods to earn more income, so sometimes baggage workers will carry goods beyond their capacity. The Facial Action Coding System (FACS) is a comprehensive anatomy-based system for visually describing all visible facial movements. It breaks down facial expressions into individual components of muscle movement, called Action Units (AUs). Given the fact that FACS can identify fatigue by analyzing human facial expressions, the authors took the initiative to explore the facial expressions of workers' fatigue with FACS automation on CERT. In this research, it was found that there was an indication of fatigue in baggage workers. This can be seen from the significant changes in the value of action units indicating fatigue for baggage workers before and after work, including an increase in the value of AU 01, AU 15, AU 20 and AU 23, while the AU 12 which is identical to the smile expression experienced a decrease in intensity in most of the subjects and the different test results from the five Action Units showed that there were significant differences between the Action Units before and after work.